CO-EXISTING MUSLIMS AND CATHOLICS: PROMOTING INTER-RELIGIOUS HARMONY THROUGH LOCAL WISDOMS IN YOGYAKARTA - Syihabuddin, Muhammad; Adila Tara Nisawanda Duha Alfani (Penamas, 2024)
This article proposes an alternative model for maintaining interfaith peace by studying the harmonious relationship between Muslim and Catholic communities in Padukuhan Pringwulung, Yogyakarta. This research aims to promote religious moderation in the context of a multicultural society. Data were obtained through in-depth interviews, observations, and documentation studies. The results show that the Pringwulung community has demonstrated a real example of social integration and interfaith harmony. Although the majority of the population is Muslim, there are harmonious religious practices through culture-based activities, such as traditional arts, traditional ceremonies, and syawalan, which involve all residents. Dukuh, RT, and RW act as the driving force in creating a shared vision that strengthens the relationship between the Muslim and Catholic communities. In addition, human values, mutual respect for differences, and mutual trust are the main foundations of maintaining harmonious relationships. Pringwulung reflects the importance of valuing diversity as social capital that strengthens community integration. This community has become not only a local model but also a global inspiration in efforts to build a safe, peaceful, and harmonious environment. Therefore, efforts to change and preserve the harmony of diversity must start from the smallest scale to create good habits that have a wide impact.